INCREASING STUDENTS’ LEARNING OUTCOMES ON THE VOLUME OF CUBES AND BEAMS LEARNING MATERIAL USING PROBLEM-BASED LEARNING MODEL - Anik Sundari; Vinencia Ika Indralin; Siti Dewi Maharani (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
This paper discusses a type of Classroom Action Research (CAR), which is based on the low students’ Math learning outcomes of students in class V.B SD Negeri 112 Palembang. The purpose is to improve students’ learning outcomes through the implementation of the Problem-based Learning model. The research was conducted in two cycles. Each cycle consists of four stages, which are planning, action, observation, and reflection. The techniques used to collect data were observation, tests, and documentation. The initial condition of the research showed that the percentage of students’ learning completeness was only limited to 10.34% (Very Less), which subsequently increased in the first cycle to 55.17% (Sufficient). The students’ learning outcomes increasingly improved in the second cycle with the percentage of students’ completeness, which reached 89.66% (Very Good). The results indicate that the application of the PBL model in learning implies a significant effect on the improvement of students’ learning outcomes in class V.B, especially on the volume of cubes and beams that have been studied. Thus, the PBL model can be said to be one of the effective learning models that can improve the student’s learning outcomes, which will be more effective if it continues to be examined as long as keeping up with the times.